Speech Acts in Indonesian Online Newspaper: A Case Study of Tribunnews - Helvira, Jenny; Hutabarat, Sabrina Wandani; Sitanggang, Lusy Agnesia; Natsir, Muhammad (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2025)
This study aims to analyze the types of speech acts and their pragmatic functions found in news headlines published by Tribunnews during March 2025. The research focuses on how language is strategically used in mass media not only to deliver information but also to influence the readers’ attitudes, emotions, and behavior. This research employs a qualitative descriptive approach, using documentation techniques for data collection. A total of 500 news headlines were analyzed based on the speech act theory of Austin (1962) and Searle (1979), which categorize speech acts into three main types: locutionary, illocutionary, and perlocutionary. The data analysis followed the interactive model by Miles, Huberman, and Saldana (2014), which includes data reduction, data display, and conclusion drawing.The findings reveal that locutionary acts dominate with 301 headlines (60.2%), indicating that the primary function of the media remains centered on delivering factual information. Illocutionary acts appear in 141 headlines (28.2%), which suggests that writers often embed subtle intentions to influence or guide readers—such as giving warnings or appeals. Perlocutionary acts, found in 58 headlines (11.6%), are intended to evoke emotional responses in readers, such as fear, surprise, or empathy. In terms of pragmatic functions, representative acts are the most prevalent at 45.6%, followed by directive and expressive functions (both at 24.4%), commissive (7.6%), and declarative (5%). These results indicate that although online news mainly serves as a factual information medium, headlines are also used to express emotions, guide public behavior, and convey institutional intentions or decisions. This research highlights that speech acts in online media are not merely descriptive but actively shape public perception and opinion, affirming the significance of discourse strategies in digital journalism.